Interference With ACSL1 Gene in Bovine Adipocytes: Transcriptome Profiling of mRNA and lncRNA Related to Unsaturated Fatty Acid Synthesis - Bai, Yanbin; Li, Xupeng; Chen, Zongchang; Li, Jingsheng; Tian, Hongshan; Ma, Yong; Raza, Sayed Haidar Abbas; Shi, Bingang; Han, Xiangmin; Luo, Yuzhu; Hu, Jiang; Wang, Jiqing; et al. (Frontiers in Veterinary Science, 2021)
The enzyme long-chain acyl-CoA synthetase 1 (ACSL1) is essential for lipid metabolism. The ACSL1 gene controls unsaturated fatty acid (UFA) synthesis as well as the formation of lipid droplets in bovine adipocytes. Here, we used RNA-Seq to determine lncRNA and mRNA that regulate UFA synthesis in bovine adipocytes using RNA interference and non-interference with ACSL1. The corresponding target genes of differentially expressed (DE) lncRNAs and the DE mRNAs were found to be enriched in lipid and FA metabolism-related pathways, according to GO and KEGG analyses. The differentially expressed lncRNA- differentially expressed mRNA (DEL-DEM) interaction network indicated that some DELs, such as TCONS_00069661, TCONS_00040771, TCONS_ 00035606, TCONS_00048301, TCONS_001309018, and TCONS_00122946, were critical for UFA synthesis. These findings assist our understanding of the regulation of UFA synthesis by lncRNAs and mRNAs in bovine adipocytes.